If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = b + -1 + -46 Reorder the terms: 11 = -1 + -46 + b Combine like terms: -1 + -46 = -47 11 = -47 + b Solving 11 = -47 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 11 + -1b = -47 + b + -1b Combine like terms: b + -1b = 0 11 + -1b = -47 + 0 11 + -1b = -47 Add '-11' to each side of the equation. 11 + -11 + -1b = -47 + -11 Combine like terms: 11 + -11 = 0 0 + -1b = -47 + -11 -1b = -47 + -11 Combine like terms: -47 + -11 = -58 -1b = -58 Divide each side by '-1'. b = 58 Simplifying b = 58
| (n+4-7)*(n+4)=30 | | y=0.5x+18 | | 11x-17x=x^2+6 | | y=3(x-a)(x+b) | | ln(x)-ln(x-8)=5 | | 104=8(r+5) | | 2x*1.25=x+6 | | lnx-ln(x-8)=1 | | 2/3y=14 | | 0.6(p-2)=0.4p+1.2 | | 0.6(p-2)=0.4p+12 | | Log(14)x=2 | | 2x+1=z | | 2x-10=3x-65 | | Y=-16t^2+424 | | -6x-3(2x-15)=45 | | 8cosx+12sinx=13 | | 3+4sin^2(x)=6 | | -2-3+2x=-8x | | 2(m-8)2+3=53 | | 1/2-3/7= | | 2x-9x-7=0 | | 625m^4-1= | | 2x^4-36=0 | | 35x^4+100x^3y-15x^2y^2= | | H(t)=16t^2+256 | | 5-2x=4x+23 | | x^2+6x-6+12=78 | | 4(2x+9)=-38+42 | | (8+7)*6-(3*4)= | | 3(2x-5)=x*x-15 | | x+71+2x+3=180 |